Broke, ill, and obese: is there an effect of household debt on health? - Keese, Matthias; Schmitz, Hendrik (Review of Income and Wealth)

Regional variation in the utilisation of ambulatory services in Germany - Kopetsch, Thomas; Schmitz, Hendrik (Health Economics)

Adaptable AC Input Phase Switching for Optimum Utilization of Various Grid Configurations supplying Power Electronic Converters and EV/HEV On Board Chargers - Schafmeister, Frank; Ide, Peter; Richter, Jörg (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A Soft-Switching Interleaved DC-DC Converter with Integrated Magnetics for High Voltage Battery Charger - Li, Ronggyuan; Njiende, Hugues; Schafmeister, Frank; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Resistorless Precharging of Boost PFCs by Phase Angle Control of Thyristors - Schafmeister, Frank; Hufnagel, Michael; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Discrete-time design of adaptive current controller for interior permanent magnet synchronous motors (IPMSM) with high magnetic saturation - Peters, Wilhelm; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Monitoring critical temperatures in permanent magnet synchronous motors using low-order thermal models - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Real-time implementation of an online Model Predictive Control for IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Efficiency-optimized Model Predictive Torque Control for IPMSM - Leuer, Michael; Ruting, Arne; Böcker, Joachim (2014 IEEE International Energy Conference (ENERGYCON))

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Power profile based selection and operation optimization of parallel-connected power converter combinations - Vogt, T.; Peters, A.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Voltage sequence control based high-current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (2014 IEEE Energy Conversion Congress and Exposition (ECCE))

A completely modular power converter for high-power high-current DC applications - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Das Erkenntnisproblem und die Mathematik. Zum Streit zwischen dem Marburger Neukantianismus und dem Neofriesianismus - Peckhaus, Volker (Wissenschaftsphilosophie im Neukantianismus. Ansätze – Kontroversen – Wirkungen)

Unsinn und Chance eines Fiktionalismus in der Logik - Peckhaus, Volker (Fiktion und Fiktionalismus. Beiträge zu Hans Vaihingers Philosophie des Als Ob)
Rezension: Zeitschrift für philosophische Forschung 69 (2015), 614–615 (Thomas Uebel)

Ernst Schröder on Pasigraphy (Dossier de la logique philosophique à la logique mathématique) - Peckhaus, Volker (Revue d’histoire des sciences)
Rezension: Math. Rev. MR3330648 (L.G. González); Zbl. Math. 1315.01023 (T.-L. Rădulescu)

In memoriam Helmar Frank

Effects of a mass finishing process on parts produced from Ultem 9085 by Fused Deposition Modeling - Fischer, M.; Schöppner, Volker (ANTEC)
Parts produced by Fused Deposition Modeling (FDM) tend to have rough and undulating surfaces with staircase effects on rounded and slanting areas of the part. This is due to the characteristics of the process. In many fields of application, high demands are made on the optical quality of the part. An improvement in the surface quality of FDM parts made of Ultem*9085 can be achieved through post-treatment with a mass finishing process. In this paper, FDM specimens are post-treated in a disk finishing unit. Influences of the mass finishing process are analyzed with regard to the dependence of surface quality on the various process parameters and on the finishing medium, grinding time and grinding speed. The finishing efficiency depends on the finishing media and decreases for lower finishing time. For all media a lower disk velocity results a smaller grinding effect, but there are clearly differences between the finishing media. The paper also discusses effects of the grinding process on the mechanical properties of the parts. Especially small part geometries and parts build in z-direction tend to break during the finishing process.

Mechanical Analysis of Lightweight Constructions manufactured with Fused Deposition Modeling - Bagsik, A.; Josupeit, S.; Schöppner, Volker; Klemp, E. (29th International Conference of the Polymer Processing Society)
Additive production techniques have the advantage of manufacturing parts without needing a forming tool. One of the most used additive manufacturing processes is "Fused Deposition Modeling" (FDM) which allows the production of prototypes and end-use parts. Due to the manufacture layer by layer, also complex part geometries can be created in one working step. Furthermore, lightweight parts with specific inner core structures can be manufactured in order to achieve good weightrelated strength properties. In this paper the mechanical behavior of lightweight parts manufactured with the 3D production system Fortus 400mc from Stratasys and the material Polyetherimide (PEI) with the trade name Ultem*9085 is analyzed. The test specimens were built up with different inner structures and building directions. Therefore, test specimens with known lightweight core geometries (e.g. corrugated and honeycomb cores) were designed. A four-point bending test was conducted to analyze the strength properties as well as the weight-related strength properties. Additionally the influence of the structure width, the structure wall thickness and the top layer thickness was analyzed using a honeycomb structure.

Ermittlung der Rotortemperatur einer Synchronmaschine mit eingebetteten Permanentmagneten für einen automobilen Traktionsantrieb mittels Beobachter basierend auf elektrischen Größen - Specht, A.

Model-Based Development of DC-DC Converters with Wide Operation Range and High Dynamics - Cao, Z.

Modeling Optimization and Control Design for LCC Resonant Converter Applied in Very Low Frequency High Voltage Generator - Hu, M.

Wirkungsgradoptimale Regelung eines elektrischen Fahrantriebes mit variabler Zwischenkreisspannung - Pohlenz, Daniel

Digital Control for Interleaved Boost Power Factor Correction (PFC) Rectifiers - Grote, T.

Modellprädiktive Regelung permanent erregter Synchronmotoren im Antriebsstrang von Automobilen - Leuer, M.

Evaluierung und Anwendung eines Emulators für elektrische Maschinen in der Entwicklung von Elektro- und Hybridfahrzeugen - Uebener, S.

Traktionsantrieb mit linearem geschalteten Reluktanzmotor für ein autonomes Bahnfahrzeug - Schneider, T.

„Tschuschen“ und „Saujuden“. Kultureller Identitätswandel in dem Roman Zwischenstationen von Vladimir Vertlib - Willeke, Stephanie (Studia theodisca XXI)

Forschung und Lehre: Freund oder Feind? - Lück, Sonja (Die Betriebswirtschaft)

Bedarfsgerechte Angebote für mehrsprachige und internationale Studierende am SchreibCenter der TU Darmstadt - Ballweg, Sandra; Arcudi, Antonio; Bernard, Julia; Hertweck, Lisa; Kimmerle, Lea Luise (Mehrsprachige Lehramtsstudierende schreiben. Schreibwerkstätten an deutschen Hochschulen)

Information processing with topologically protected vortex memories in exciton-polariton condensates - Sigurdsson, H.; Egorov, O. A.; Ma, Xuekai; Shelykh, I. A.; Liew, T. C. H. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Biliteratlität - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Dominante Sprache - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Lernersprache - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Sprachliche Identität - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Sprachlernbewusstheit - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Pidginisierung - Efing, Christian; Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Sprachbildung in allen Fächern - Beese, Melanie; Benholz, Claudia; Chlosta, Christoph; Gürsoy, Erkan; Hinrichs, Beatrix; Niederhaus, Constanze; Oleschko, Sven

Verpasste Lerngelegenheit? Eine qualitative Befragung mehrsprachiger Jugendlicher zur Nutzung von Schulbuchtexten und Konsequenzen für die interkulturelle Lehrerbildung - Niederhaus, Constanze (Methoden – Strukturen – Gestaltung: Lerngelegenheiten und Lernen in der „interkulturellen Lehrerbildung“)

Sprachförderung - Niederhaus, Constanze; Günther, Katrin (Leitfaden individuelle Förderung)

Horky, Philip Sidney, "Plato and Pythagoreanism", Oxford University Press: Oxford 2013 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Leibniz, G.W., "The Leibniz–De Volder Correspondence. With Selections from the Correspondence between Leibniz and Johann Bernoulli, translated, edited, and with an introduction by Paul Lodge", Yale University Press: New Haven and London 2013 (The Yale Leibniz) - Peckhaus, Volker (Mathematical Reviews)

Barendregt, Henk, “Foundations of Mathematics from the Perspective of Computer Verification”, in: Mathematics, Computer Science and Logic–A Never Ending Story, Cham: Springer 2013, 1–49 - Peckhaus, Volker (Mathematical Reviews)

Schreiben im Blick. Schriftliche Formen der sprachlichen Tätigkeit aus dialogischer Perspektive - Karsten, Andrea

Writing: Movements of the self - Karsten, Andrea (Theory & Psychology)
This article presents analyses of excerpts from a study on writing conducted in a dialogical perspective. The study’s material was collected by the auto-confrontation method: writers were videotaped during their work and afterwards confronted with their writing activities. Microanalysis of the material attends to how inner dialogues during writing are “refracted” (Voloshinov) in auto-confrontation. Bakhtin’s notion of the chronotope (time-and-space) as the main tool of analysis helps to discern the changing contexts and position constellations utterances are valid for. It thus sheds light on the positioning movements performed by the writing selves through language. The analyses show various utterance movements traversing the chronotopes involved, ranging from refractions of movements between the writers’ inner dialogues and their texts to retrospective imperatives with a developmental potential. This “dialogical volume” of speech activity presenting itself in writing can contribute to our understanding of the interplay of language and the self.
Keywords: auto-confrontation; chronotope; inner dialogue; microanalysis; positioning; writing

Schreiben ist Dialog. Ergebnisse und Implikationen einer Studie zum ,schreibbegleitenden‘ Sprechen - Karsten, Andrea (JoSch – Journal der Schreibberatung)

Hegemoniale Männlichkeit. Herrschergestalten in Fritz Langs Film Die Nibelungen - Somogyi, Peter (Durchkreuzte Helden. Das ‘Nibelungenlied‘ und Fritz Langs Film ‘Die Nibelungen‘ im Licht der Intersektionalitätsforschung (GenderCodes 17))

Michael Prestwich: Ritter. Der ultimative Karriereführer gelesen von Martin Falk - Somogyi, Peter (literaturkritik.de Nr. 2, Februar 2014)